In vitro conservation of mangaba native to Brazilian Cerrado - Pires, Danyela Cristina Marques; Trento, Sabrina de Matos; Paula, Mariana Silva Pereira de; Asmar, Simone Abreu; Luz, José Magno Queiroz; Souza, Ana Valéria Vieira de (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Mangaba (Hancornia speciosa var. gardneri) is an important fruit tree, because it ensures sustenance and provides food for several extractive families. Currently, mangaba is threatened with extinction and due to its importance, the Brazilian Ministry of the Environment, has been encouraging the development of studies that can result in conservation strategies for this genetic resource. Thus, the objective of this work was to accomplish the slow growth in vitro conservation of mangaba nodal segments by changes in temperature and in culture medium, and after that, to conduct the growth recovery of the explants. In the in vitro conservation stage, two experiments were made to test the temperatures of 25 and 20ºC, in which mangaba nodal segments were inoculated in transparent glass jars containing MS and WPM media with 100 and 50% salt concentration, being evaluated at 45 and 90 days of in vitro conservation. In order to verify the growth recovery of the explants, these were transferred to multiplication medium, and evaluated at 60 days. Explants conserved at 20°C showed small and chlorotic leaves compared to those conserved at 25°C. The reduction of the conservation temperature provided less development of the explants without affecting the survival rate. Explants conserved in WPM medium showed better responses to growth recovery. The results show that mangaba nodal segments conserved for 90 days in WPM medium with 50% salt concentration and temperature of 20°C presented low metabolism and a good response to growth recovery stage.